Modeling and Simulation of Off-Grid Power Generation System Using Photovoltaic - Himanshu Sharma; Nitai Pal; Pradip Kumar Sadhu (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Off-Grid is a part of the power distribution system which uses renewable energy based of power generation connected to the grid system. Multi energy power generation is composed of renewable energy systems including photovoltaic, wind turbine, energy storage and local loads. Test bed of an Off-Grid system is the technique to ensure stable operation during faults and various network disturbances in grid and islanding connected mode. In this paper the Off-Grid using renewable energy consist of a 3 kW photovoltaic, with 30 pieces of 12V, DC/DC converter, charge controller for battery, single phase DC/AC inverter and  various loads (resistor, capacitor, inductor) are develop. The AC buses 240V voltage include with isolation transformer to simulate the grid voltage level by Matlab/Simulink software. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7061